Diastereoselective Synthesis of Spirodihydrobenzofuran Analogues of the Natural Product Filifolinol. Issue 48 (28th December 2020) - Becerra‐Ruiz, Martin; Galdámez, Antonio; Modak, Brenda; Vilches‐Herrera(s), Marcelo
Abstract: Filifolinol is a natural occurring spirodihydrobenzofuran isolated from the resinous exudates of Heliotropium filifolium, a Chilean endemic shrub. Filifolinol and some of its derivatives have shown interesting biological activities against pathogens that attack salmonid species. Whereas the synthesis of spirodihydrobenzofurans has been limited to the use of an ortho allylphenol unit herein we report a different approach based on a C−H activation/C−O cyclization reaction for the synthesis of analogues of Filifolinol. Moreover, a diastereoselective approach was developed using the different facial preference of hydride species and organolithium compounds towards cyclic ketones. Abstract : The diastereoselective synthesis of analogues of the natural product Filifolinol was achieved in only 3 synthetic steps by using cheap and commercially available starting materials. The diastereoselective approach was developed using the different facial preference of hydride species and organolithium compounds towards cyclic ketones. Whereas the spirocyclization step was performed using a Palladium C−H activation/C−O cyclization reaction.